Quality assessment of imported fish retailed in Sri Lanka - Dilrukshi, P.G.M.; Arachchi, G.J.G.; Ginigaddarage, P. H.; Ariyawansa, K.W.S.; Wickramasinghe, I.; Hettiarachchi, K.S.; Abhayarathne, S.; Perera, R. (My University, 2017)
attached

The present study assessed the quality of selected varieties of imported fish by testing theconcentration of formaldehyde, total volatile basic nitrogen (TVB-N) content and Escherichiacoli (E.coli).The samples included four of Indo-Pacific sailfish (Istiophorus platypterus), five ofblue mackerel (Scomberaus tralasicus), nine of bullet tuna (Auxis rochei), seven of sword fish(Xiphias gladius), seven of squids (Loligodu vauceli) and four of Indian Scad (Decapterusrusselli) available in retail outlets in Gampaha District in Sri Lanka. Formaldehyde content wasassessed only in sword fish, squids, Indian scad and bullet tuna species and showed values inthe range of 0.917 to 3.34 mg/kg. There was a significant difference (p<0.05) between the meanformaldehyde concentrations of swordfish and bullet tuna. All fish samples revealedformaldehyde concentration lower than specified limit of 5 mg/kg (Food Regulation No.1646/19: Formaldehyde in fish, 2010). Mean TVB-N content of bullet tuna, squids, Indo-Pacificsail fish, sword fish, blue mackerel and Indian scad were 36.00, 6.65, 9.00, 20.60, 10.82 and137.4 mg/100g, respectively and the mean values of these fish varieties were significantlydifferent each other (p<0.05). Majority of the imported fish samples (27/36) had E. coli levels ofgood quality (75.76%) according to ICMSF (1986) standards while the remaining fish (9/36)were marginally acceptable (24.24%
Keywords: E.coli; Formaldehyde; Imported fish; Total volatile basic nytrogen